Differential autophagic effects triggered by five different vertebrate iridoviruses in a common, highly permissive mandarinfish fry (MFF-1) cell model. (February 2016) - Qi, Hemei; Yi, Yang; Weng, Shaoping; Zou, Weibing; He, Jianguo; Dong, Chuanfu
Abstract: Autophagy of five vertebrate iridoviruses, including one megalocytivirus (infectious spleen and kidney necrosis virus, ISKNV) and four ranaviruses (Chinese giant salamander iridovirus, CGSIV; Tiger frog virus, TFV; Grouper iridovirus, GIV; and Largemouth bass virus, LMBV) were investigated in a common, highly permissive mandarinfish fry (MFF-1) cell model. The results showed marked autophagosome formation in GIV- and LMBV-infected cells but not in ISKNV-, CGSIV- and TFV-infected MFF-1 cells. Strong evidence for the autophagosomes was provided by transmission electron microscopy, the detection of mandarinfish microtubule-associated protein 1 light chain 3B (mLC3)-based fluorescent dot formation and mLC3-I/mLC3-II conversion was provided by Western blotting. Pharmacological tests indicated that autophagy plays an antiviral role during GIV or LMBV infection. Collectively, our data are the first to show that antiviral autophagic effects can be triggered by GIV and LMBV but not by ISKNV, TFV and CGSIV in a common susceptible cell model. These results suggest that differential host–virus interaction strategies may be utilized against different vertebrate iridoviruses; they also indicate the potential effectiveness of an antiviral treatment that modulates autophagy to control iridoviral infections, such as GIV and LMBV. Highlights: Autophagy of five different vertebrate iridoviruses were investigated. Autophagy could not be induced by ISKNV, the type species in genus Megalocytivirus . Differential levels of autophagy were observed for four different ranaviruses. Autophagy could be triggered by GIV and LMBV but not by TFV and CGSIV. Antiviral autophagic effects on GIV or LMBV infection was confirmed by pharmacological tests.